(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In article the concept of post-religion designed, proceeding from methodological messages of Traditionalist school which are also proved in article, in comparison with the other methodological approaches finding the insolvency at an assessment of spirituality of the Postmodernity is considered. The post-religion which has departed from a rectilinear modernist secularization, is shown in various cuts (deconstructivism, splitting, virtualization, collaging); the post-religion consistently reduces traditional spirituality to the plane imitation which is not allowing the modern adherent of traditional belief to open vertical measurement of Tradition, erecting to Sacred. Such approach shows post-religion top of world desacralization process. The postreligion - as the spiritual sphere of the Postmodernity - is a deviation from the secular program to Tradition to which the Modernity consistently opposed itself. However, the post-religion instead of Tradition creates a set of various imitations and the simulations, quite successfully applying for a role of traditional spirituality in the modern globalized and secularizationed world. Keywords: post-religion, Postmodernity, Tradition, traditionalism, simulacrum, deconstruction, rhizome, desacralization, secularization.